2007
DOI: 10.1186/1471-2164-8-438
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic gene expression in fish muscle during recovery growth induced by a fasting-refeeding schedule

Abstract: Background: Recovery growth is a phase of rapid growth that is triggered by adequate refeeding of animals following a period of weight loss caused by starvation. In this study, to obtain more information on the system-wide integration of recovery growth in muscle, we undertook a timecourse analysis of transcript expression in trout subjected to a food deprivation-refeeding sequence. For this purpose complex targets produced from muscle of trout fasted for one month and from muscle of trout fasted for one month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
80
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 38 publications
16
80
0
Order By: Relevance
“…Hybridization of microarrays and raw data production " cDNA nylon membrane microarrays were generated by CRB GADIE (http://crb-gadie.inra.fr/) as described previously (Rescan et al 2007). Prehybridization of the membranes was performed at 65 8C for 4 h in 5!…”
Section: Steroid Measurementmentioning
confidence: 99%
“…Hybridization of microarrays and raw data production " cDNA nylon membrane microarrays were generated by CRB GADIE (http://crb-gadie.inra.fr/) as described previously (Rescan et al 2007). Prehybridization of the membranes was performed at 65 8C for 4 h in 5!…”
Section: Steroid Measurementmentioning
confidence: 99%
“…Fasting induces a loss of muscle mass resulting from the breakdown of muscle proteins, which involves several proteolytic systems such as the autophagy-lysosome and the ubiquitin-proteasome systems (Bonaldo and Sandri, 2013;Bodine and Baehr, 2014). Some studies have addressed changes in transcriptional regulation associated with muscle atrophy (Salem Rescan et al, 2007), but less is known about concomitant changes in muscle fibre production. In this study, we show that GFP-expressing small myofibres are still produced in the muscle of fasted trout and are as numerous as they are in the muscle of well-fed trout.…”
Section: Discussionmentioning
confidence: 99%
“…Recovery growth in muscle in response to fasting and re-feeding was studied in trout using a cDNA microarray and revealed a complex response. The principal groups of upregulated transcripts were involved in protein catabolism, myofibre and muscle remodelling and regulation of transcription (Rescan et al, 2007). Other studies of re-feeding in fish have shown enhanced muscle expression of kinases involved in the mTOR signalling pathway known to promote protein accretion in mammalian muscle (Seiliez et al, 2008).…”
Section: Consequences Of Maternal Nutritionmentioning
confidence: 94%